(untitled) (Research, Society and Development, 2021)
Objective: To identify the clinical manifestations of the gastrointestinal tract in patients affected by COVID-19 and monitored by the Municipal Health Department of Aracaju. Methodology: retrospective, cross-sectional, survey-type study, carried out from March to July 2020, based on information contained in a database of the Health Department of Aracaju. Sample composed of 3,342 patients registered in the telemonitoring program of the Department, who were tested and confirmed by RT-PCR for SARS-CoV-2. Data analyzed using percentage frequency, Pearson, Shapiro-Wilks and Mann-Whitney tests. Adopted significance level of 5%. Results and Discussion: 938 (27.36%) patients with gastrointestinal manifestations were registered: diarrhea 637 (18.58%), abdominal pain 158 (4.61%), nausea 156 (4.55%), vomiting 89 (2 .6%) and anorexia 119 (3.47%). With a mean age of 39.1 (±14.8) years, 563 (60%) were female and 930 (99.9%) lived in Aracaju or nearby. The mean age of severe cases was 55.5 (±18.9) years and 53.9% were male. The average duration of gastrointestinal symptoms was 6.5 days. All severe cases were hospitalized and, of these, 4 (0.5%) died. Main comorbidities associated with severe cases (p<0.05): cardiovascular diseases, diabetes mellitus, chronic kidney disease, cancer and neurological diseases. Conclusion: there was an important association between gastrointestinal symptoms in patients with COVID-19, especially in young and female patients. The presence of previous comorbidities was a statistically significant factor for the appearance of digestive tract manifestations.